Academic speech on the decentralization a theoretical approach: classic and contemporary - Vargas Morales, Zenón Eduardo (2009)
The present article makes a revision of the studies related to the theory of the decentralization and it is classified according to the theoretical approach that is approached. Also, one picks up the points of view of Peruvian investigators (historians, economists and sociologists) that in the last years comes discussing on the process of decentralization in Peru. Of that way, the originating studies of decentralization of the classic ones of social sciences with their respective approaches are identified: economic, sociological, politológico. In each of them the central preoccupation around the decentralization and the democracy is examined. The objective is the necessity to motivate the interdisciplinary and compared studies, in order to include/ understand the resistances of the decentralization process.